Optimizing Inspection Strategies to Enforce Organic Farming Standards - Christian Lippert; Alexander Zorn; Stephan Dabbert (German Journal of Agricultural Economics (GJAE), 2016)
The organic market depends on an effective and efficient certification system. Control bodies or authorities are pivotal to this system. From a social point of view, our objective is to theoretically optimize inspection strategies. For this, sanctions and inspection frequencies have to be implemented in a way that the net social damage arising from farmers' non-compliance with an organic standard will be minimized. In scenarios that combine different kinds of social damages, fines and compliance cost distributions for an assumed set of farms we use Monte Carlo simulations to model farmers' non-compliance and resulting social damages. Depending on potential reputation losses and compliance cost variability among farms we identify different adequate control frequencies.
Keywords: 330